Computer technology for people with visual impairment : a study for Malaysian Association for the Blind (MAB) / Roziana Tamerin - Tamerin, Roziana (Faculty of Computer and Mathematical Sciences, 2007)
People with visual impairment face difficulties in accessing computer. They need a specific devices or assistive technology that enables them to access computer. There are many assistive technologies that had been introduced mostly at First World coimtry. For example, assistive technology for visual impairment and sighted impaired people such as computer screen readers, screen magnifiers. Braille displays, voice input software. Braille embossers or Braille printer, stand alone products and so on. This kind of assistive technology have given such a big contribution for visual impairment and sighted impaired people. It is because, through this assistive technology, they can experience a growth of technology like normal people and thus can increase their computer literacy. So this thesis purposely will identify the characteristics of computer equipments used and also the visually impaired people acceptance towards these technologies. For this thesis, the scope for the research will focus on the Malaysian Association for The Blind (MAB). Questionnaire distributed and interview sessions conducted will produce significant results and findings towards achieving the objectives of this thesis.